2012
DOI: 10.1063/1.4769788
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent magnetotransport phenomena in a hybrid Fe/SiO2/p-Si structure

Abstract: We report the large magnetoimpedance effect in a hybrid Fe/SiO2/p-Si structure with the Schottky barrier. The pronounced effect of magnetic field on the real and imaginary parts of the impedance has been found at temperatures 25–100 K in two relatively narrow frequency ranges around 1 kHz and 100 MHz. The observed frequency-dependent magnetotransport effect is related to the presence of localized “magnetic” states near the SiO2/p-Si interface. In these states, two different recharging processes with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In the dc mode, the MR effect is weak even in high magnetic fields of up to 9 T. 17 For this reason, we started studying the Schottky diodes with the Mn electrode with impedance (Z = R ac + iX, where R ac and X are the real and imaginary parts of the impedance, respectively) and magnetoimpedance measurements. At reverse and low forward bias V b (V b < V c b ≈ 2 V), we obtained the results similar to those reported in 18,20 for the structures with Fe.…”
Section: A Magnetoimpedance: Low Biassupporting
confidence: 80%
See 1 more Smart Citation
“…In the dc mode, the MR effect is weak even in high magnetic fields of up to 9 T. 17 For this reason, we started studying the Schottky diodes with the Mn electrode with impedance (Z = R ac + iX, where R ac and X are the real and imaginary parts of the impedance, respectively) and magnetoimpedance measurements. At reverse and low forward bias V b (V b < V c b ≈ 2 V), we obtained the results similar to those reported in 18,20 for the structures with Fe.…”
Section: A Magnetoimpedance: Low Biassupporting
confidence: 80%
“…Our studies on lateral devices and Schottky diodes based on the Fe/SiO 2 /p(n)-Si hybrid structures showed that the interface states localized in the SiO 2 /p(n)-Si interfacial region make a significant contribution to magnetotransport. [17][18][19][20] These states are involved in recharging and their energy structure is rearranged by a magnetic field. However, this is apparently not the only possible mechanism, since it does not explain the variety of MR effects observed in the MIS-structure-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…17 Previously, we reported the unusual magnetotransport properties of simple devices based on the Fe/SiO 2 /p-Si hybrid structure on a p-type semiconductor substrate. [18][19][20] We investigated the magnetoimpedance, but the value of the effect was much smaller. In addition, due to the features of the spectrum of the interface states at the SiO 2 /p-Si interface, we failed to explicitly separate and analyze the contribution of the magnetosensitive centers to the magnetoimpedance.…”
mentioning
confidence: 99%
“…To study the Fe 3 Si/Si interface electric properties, a diode was fabricated with an ohmic contact on the substrate backside ( figure 3(d)), for which the measurements of I-V characteristics were performed as well as the temperature and frequency dependences of the real (Re |Z|) and imaginary (Im |Z|) parts of impedance. Studies of charge transport were performed at a cryogenic probe station Lakeshore EMPX-HF 2 and a homebuilt facility based on a helium cryostat and electromagnet [41,42] using a Keithley 2634b SourceMeter and Agilent E4980A for dc and ac measurements, respectively, in the temperature range from 4.2 K to 300 K.…”
Section: Methodsmentioning
confidence: 99%